A taxonomic study of the genus Lotononis (DC.) Eckl. & Zeyh. (Fabzceae, Crotalarieae) - Van Wyk, Ben-Erik (Department of Biological Sciences, 2016)
The approach and methods used in a taxonomic study of the genus Lotononis (DC.) Eckl. & Zeyh. and related genera of the tribe Crotalarieae (Benth.) Hutch. are briefly introduced in Part 1. Morphological, cytological and chemical data was analyzed by cladistic methods to provide a sound basis for the generic delimitation of Lotononis and to formulate a natural infrageneric classification. The generic limits of Lotononis and its relationships with 14 other genera of the Crotalarieae are discussed in Part 2. Detailed morphological studies by Polhill (1976) has shown the widespread occurrence of convergence and conflicting character information in the tribe. Only a few of the genera are monothetic taxa and very few characters are available for cladistic analyses. This is not so much due to a lack of data but rather to ambiguity as to how morphological characters should be interpreted. It was therefore decided to concentrate on a study of alkaloids to test the predictivity of the present generic delimitations in the Crotalarieae. With the exception of Crotalaria L., virtually nothing was known about the alkaloids of the tribe (Mears & Mabry 1971, Kinghorn & Smolenski 1981). In the tribe Genisteae, alkaloid patterns show a high degree of conformity with evolutionary patterns based on morphological evidence (Polhill 1976) and the value of alkaloids as a generic character in the Leguminosae is well known (Kinghorn & Smolenski 1981). It seemed that more insight into generic relations in the Crotalarieae could be gained by concentrating on a hitherto much neglected field rather than to duplicate the detailed morphological studies of Polhill (1976). It was also clear that meaningful conclusions could be made about generic relationships, because the biogenetic pathways along which quinolizidine and pyrrolizidine alkaloids are formed are rather well known. The survey of major alkaloids (Appendices 1 to 11) indeed led to a much better understanding of the intricate relationships in the Crotalarieae, and made it possible to present a well supported and almost fully resolved cladogram for the tribe as a whole.